PENELITIAN PENDIDIKAN PADA MADRASAH - Aziz, Abdul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Educational research is crucial to develop sustainable educational program of Madrasah. Educational research provides important data to defie the plan, evaluate the program, and promote enjoyable learning environment in Madrasah. Educational research in Madrasah still faces some problems such as limited budget, being reluctant to provide data and be research subject among principals and teachers of Madrasah. The researcher has to know research methodology both quantitative and qualitative method to conduct research activity in Madrasah. The valid and reliable fidings in educational research are important for Madrasah to improve educational quality of Madrasah.Keywords: educational research, madrasah